2014
DOI: 10.1063/1.4870626
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity and photo-detection response of multiferroic bismuth iron oxide

Abstract: Articles you may be interested inA large polarization in Ce-modified bismuth ferrite thin films

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…To determine the lifetimes of slow and fast charge carriers during the growth and decay process, the ON/OFF currents, were fitted to the model below. 52,53,54 Equation 1 is used to fit the experimental data of decay process.…”
Section: Photo-response Time Studymentioning
confidence: 99%
“…To determine the lifetimes of slow and fast charge carriers during the growth and decay process, the ON/OFF currents, were fitted to the model below. 52,53,54 Equation 1 is used to fit the experimental data of decay process.…”
Section: Photo-response Time Studymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] BiFeO 3 (BFO) is one of the most studied lead free room temperature multiferroic perovskite oxide because of its fascinating physical properties; large polarization (90µC/cm 2 ), weak ferromagnetism, and optical bandgap (~2.67 eV) [9][10][11][12] lies in visible region, make it suitable multifunctional material for spintronics, data storage, sensors, and optoelectronic applications. [13][14][15][16][17] Recently, the single phase BFO thin films showed promising potential towards ferroelectric photovoltaic (Fe˗PV) application due to enhanced room temperature ferroelectricity and small optical bandgap. [17][18][19][20] Among other wide bandgap Fe˗PV materials (i.e., BaTiO 3 , LiNbO 3 and Pb(Zr,Ti)O 3 ), BFO exhibits large open circuit voltage (V OC ), tunable output, and switchable photodiode effect 6,[9][10][11] .…”
mentioning
confidence: 99%
“…[13][14][15][16][17] Recently, the single phase BFO thin films showed promising potential towards ferroelectric photovoltaic (Fe˗PV) application due to enhanced room temperature ferroelectricity and small optical bandgap. [17][18][19][20] Among other wide bandgap Fe˗PV materials (i.e., BaTiO 3 , LiNbO 3 and Pb(Zr,Ti)O 3 ), BFO exhibits large open circuit voltage (V OC ), tunable output, and switchable photodiode effect 6,[9][10][11] . It has been reported that the polarization flipping induced modulation of Schottky-like barrier at metal/ferroelectric interface leads switchable PV and diode effect in BFO thin film heterostructures.…”
mentioning
confidence: 99%
“…However, the response time of the GaN nanorods network was several order higher in the range of 100 ms compared to bulk photovoltaic devices and detectors (seconds per milliseconds). [41][42][43][44][45] The capacitance characteristics of the nanorods network demonstrate the presence of NC, a suitable candidate for metamaterials.…”
Section: Discussionmentioning
confidence: 99%